1984
DOI: 10.1902/jop.1984.55.9.516
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Tension (pO2) in Untreated Human Periodontal Pockets

Abstract: The purpose of this study was to assess the oxygen tension in untreated human periodontal pockets and test the hypothesis that the subgingival environment is anaerobic in nature. Twenty‐six patients with advanced chronic inflammatory periodontal disease participated. A total of 111 untreated pockets, 5 to 10 mm in depth, were selected for the pO2 measurements. Pocket depths, Plaque‐Index and Gingival‐Index were recorded. The pO2 at the base of the 111 pockets ranged from 5 to 27 mm Hg, with an average of 13.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 15 publications
4
122
0
1
Order By: Relevance
“…However, it should be noted that deoxyhaemoglobin was not formed during incubation of oxyhaemoglobin with bacterial cells and it must be concluded that the ligated oxygen was used up during the process of µ-oxo bishaem generation from the oxygenated protein. The periodontal pocket, which is the preferred habitat of P. gingi alis [27], is not totally anaerobic [28], and partial pressures of O # of $ 20 mmHg have been measured [29]. This would yield a haemoglobin oxygen saturation of $ 25 %.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that deoxyhaemoglobin was not formed during incubation of oxyhaemoglobin with bacterial cells and it must be concluded that the ligated oxygen was used up during the process of µ-oxo bishaem generation from the oxygenated protein. The periodontal pocket, which is the preferred habitat of P. gingi alis [27], is not totally anaerobic [28], and partial pressures of O # of $ 20 mmHg have been measured [29]. This would yield a haemoglobin oxygen saturation of $ 25 %.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well appreciated that low oxygen tension is common at inlamed periodontitis sites [4]; thus, the corresponding local immune responses must adapt to the hypoxic challenges. As mentioned above, hypoxia plays an important role in modulating the cellular activities of innate and adaptive immunity, so the impact of low pO 2 in periodontal immune responses is quite signiicant.…”
Section: Hypoxia and Periodontal Immunitymentioning
confidence: 99%
“…The epithelial cells in both oral mucosa and the gut are relatively hypoxic [4,77]. The corresponding oxygen gradient between the epithelium and subepithelial perfusion in turn provides a matching cellular HIF-1α gradient in the tissues involved and perhaps the respective physiological function in cellular homeostasis.…”
Section: Hif and Epithelial Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, to model the microaerophilic conditions found in periodontal pockets (Mettraux et al, 1984), the CDFF was operated by continuous flushing (60 cm 3 /min) with a gas mixture consisting of 95% N 2 , 3% CO 2 , 2% O 2 . The growth medium used to enable propagation of biofilms from the microcosm plaques consisted of RPMI medium (60%) (Sigma, Poole, UK) and horse serum (40%) (Oxoid, Basingstoke, UK) supplemented with 0.5 µg menadione/ml and 5.0 µg hemin/ml.…”
Section: Production Of Microcosm Subgingival Dental Plaquesmentioning
confidence: 99%